VBP1 promotes tumor proliferation as a part of the hypoxia-related signature in esophageal squamous cell carcinoma - Miao, Huikai; Gao, Wuyou; Zhong, Leqi; Li, Hongmu; Chen, Dongni; Xu, Chunmei; Wen, Zhesheng; Chen, Youfang (Human cell : official journal of Human Cell Research Society, 2024)
Esophageal squamous cell carcinoma (ESCC) is a common malignant tumor in East Asia. Hypoxia, a hallmark of solid tumors, significantly alters redox homeostasis inside tumor microenvironment. This alteration drives tumor proliferation, invasion, and metastasis, leading to poor prognostic outcomes. However, the role of hypoxia-related genes in ESCC remains poorly understood. We employed RNA sequencing to identify differentially expressed genes in ESCC. Clinical data, transcriptome profiles, and a hypoxia-related gene set were extracted from open-source databases. A prognostic model was constructed using least absolute shrinkage and selection operator (LASSO) regression, which was then validated through Cox regression analysis. Within this prognostic model, we pinpointed and investigated a key hypoxia-related gene affecting prognosis. The gene's expression was validated using real-time PCR and immunohistochemistry in both esophageal carcinoma and normal tissues. Tumor proliferation was examined through in vitro and in vivo assays, including the Cell Counting Kit-8, EdU, colony formation, and subcutaneous tumor models. A robust four-gene prognostic model (VBP1, BGN, CDKN1A, and PPFIA1) was successfully constructed and validated. Among these, VBP1 emerged as a key gene, exhibiting high expression levels that correlated with poor prognosis in ESCC. Functional experiments confirmed that VBP1 significantly accelerated tumor proliferation both in vitro and in vivo. VBP1 is identified as a pivotal gene within the hypoxia-related prognostic signature, and it significantly promotes tumor proliferation in ESCC.